Yield response of a polycropping system with maize to fermented foliar fertilizers - Ebel, Roland (CIENCIA ergo-sum; Vol. 27 Núm. 3 (2020): CIENCIA ergo-sum (noviembre 2020-febrero 2021)DO - 10.30878/ces.v27n3a8, 2020)
Anaerobically fermented foliar fertilizers (FFF) are made of local plant or animal inputs. The impact of four different FFF formulations on the output of an intercropping system with fava bean, maize, and squash was assessed in the Toluca Valley, Central Mexico. A fertilizer made of cow manure and fermented agave cactus juice had an elevated N and P content and resulted in the highest maize output. A fertilizer made of cow manure and maize stalks contained most K and delivered the highest squash yield. A FFF made of cow manure and stinging nettle delivered the highest fava bean output. There are no ideal formulations of FFF, but their formulation depends on available resources and treated crops.